Improvements in the quality of advanced life support and patient outcome after implementation of a standardized real-life post-resuscitation feedback system. (November 2017) - Hubner, Pia; Lobmeyr, Elisabeth; Wallmüller, Christian; Poppe, Michael; Datler, Philip; Keferböck, Markus; Zeiner, Sebastian; Nürnberger, Alexander; Zajicek, Andreas; Laggner, Anton; Sterz, Fritz; Sulzgruber, Patrick
Abstract: Background: Educational aspects in the training of advanced life support (ALS) represent a key role in critical care management of patients with out-of-hospital cardiac arrest (OHCA) and received special attention in guidelines of various international societies. While a positive association of feedback on ALS performance in training conditions is well established, data on the impact of a real-life post-resuscitation feedback on both ALS quality and outcome remain scarce and inconclusive. We aimed to elucidate the impact of a standardized post-resuscitation feedback on quality of ALS and improvements in patient outcome, in a real-life out-of-hospital setting. Methods: We prospectively enrolled and analyzed 2209 patients presenting with OHCA receiving resuscitation attempts by the municipal emergency medical service (EMS) of Vienna over a two-year period. A standardized post-resuscitation feedback protocol was delivered to the respective EMS-team to elucidate its impact on the quality of ALS. Results: We observed that both chest compression rates and ratios were in accordance to recommendations of recent guidelines. While interruptions of chest compressions longer than 30 s declined during the observation period (−6.5%) rates of the recommended chest compressions during defibrillator-charging periods increased (+8.9%). Since the percentage of ROSC and 30-day survival remained balanced, the frequencies of both survival until hospital discharge (+6.3%) and favorable neurological outcome (+16%) in survivors significantly increased during the observation period. Conclusion: Improvements in the quality of advanced life support as well the patient outcome were observed after the implementation of a standardized post-resuscitation feedback protocol.